2018
DOI: 10.1371/journal.pone.0197326
|View full text |Cite
|
Sign up to set email alerts
|

General discussion of data quality challenges in social media metrics: Extensive comparison of four major altmetric data aggregators

Abstract: The data collection and reporting approaches of four major altmetric data aggregators are studied. The main aim of this study is to understand how differences in social media tracking and data collection methodologies can have effects on the analytical use of altmetric data. For this purpose, discrepancies in the metrics across aggregators have been studied in order to understand how the methodological choices adopted by these aggregators can explain the discrepancies found. Our results show that different for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 18 publications
2
72
0
2
Order By: Relevance
“…CED also describes a short activity period (2017-2018), but with significant increases. Thus, in 2017, it showed an average coverage of 9.1% (Ortega, 2018a;2018b;Costas, 2018), which rose to 21.2% in 2018 (Ortega, 2019).…”
Section: Coveragementioning
confidence: 98%
See 3 more Smart Citations
“…CED also describes a short activity period (2017-2018), but with significant increases. Thus, in 2017, it showed an average coverage of 9.1% (Ortega, 2018a;2018b;Costas, 2018), which rose to 21.2% in 2018 (Ortega, 2019).…”
Section: Coveragementioning
confidence: 98%
“…However, from 2016 to 2017 only three services were used, Mendeley, Altmetric.com and PlumX. Because Lagotto is not implemented in important publishers other than PLoS, it became a limited tool for altmetric studies and was used only in one-time cases Costas, 2018). ImpactStory stops provide a public API, making it hard to obtain random representative samples.…”
Section: Providersmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, in what ways do the data providers used in scientometric analysis provide discrepant data? Zahedi and Costas (2018), for instance, conducted the most exhaustive comparison of altmetric providers and found that coverage of publications between them varies widely.…”
Section: Commentarymentioning
confidence: 99%